Bide Nu Æt Gode Þæt Ic Grecisc Cunne: Attitudes to Greek and the Greeks in the Anglo-Saxon Period - Timofeeva, Olga (Studia Anglica Posnaniensia, 2016)
This paper uses these data, supplementing them with searches in the Dictionary of Old English Web Corpus, Brepolis Library of Latin Texts - Series A, monumenta.ch and Medieval Latin from Anglo-Saxon Sources, and analyses lexical and syntactic strategies of the Greek outgroup construction in Anglo-Saxon texts. It looks at lexemes denoting ‘Greek’ and their derivatives in Anglo-Latin and Old English, examines their collocates and gleans information on attitudes towards Greek and the Greeks, and on membership claims indexed by Latin-Greek or English-Greek code-switching, by at the same time trying to establish parallels and influences between the two high registers of the Anglo-Saxon period.